Optimizing Education Through Website-Based Learning Media: Implementation in Junior High Schools - Utami, Listia; Andri Majid; Bobur Sobirov; Jaffer Basha (Ceddi Journal of Education, 2024)
This study aims to design and implement a website-based learning and information management system for MTs KSM Kalupapi. The system serves as a comprehensive platform for facilitating school information dissemination and supporting online learning processes. Employing the UML approach, the system was developed with intuitive interfaces and structured data management to ensure accessibility and functionality for diverse user groups. It accommodates school principals for administrative oversight, teachers as content managers, students for accessing educational materials and assignments, and parents for monitoring their children's academic progress. The system underwent rigorous testing using the black box method to validate its functionality, ensuring accurate outputs aligned with specified requirements. Survey feedback from users indicated exceptional satisfaction, with an average score of 99% and overwhelmingly "strongly agreed" responses across all evaluation metrics. These results highlight the system's effectiveness in enhancing learning efficiency and streamlining information management within the school environment. This study underscores the transformative potential of website-based learning systems in modern education. It also offers a foundation for future enhancements, such as integrating advanced features, adapting for broader educational contexts, and scaling for use in other institutions, thereby promoting innovation and accessibility in education.